Stimulation of Mytilus galloprovincialis Hemocytes With Different Immune Challenges Induces Differential Transcriptomic, miRNomic, and Functional Responses - Moreira, Rebeca; Romero, Alejandro; Rey-Campos, Magalí; Pereiro, Patricia; Rosani, Umberto; Novoa, Beatriz; Figueras, Antonio (Frontiers in Immunology, 2020)
Mediterranean mussels (Mytilus galloprovincialis) are marine bivalve molluscs with high resilience to biotic and abiotic stress. This resilience is one of the reasons why this species is such an interesting model for studying processes such as the immune response. In this work, we stimulated mussel hemocytes with poly I:C, β-glucans, and LPS and then sequenced hemocyte mRNAs (transcriptome) and microRNAs (miRNome) to investigate the molecular basis of the innate immune responses against these pathogen-associated molecular patterns (PAMPs). An immune transcriptome comprising 219,765 transcripts and an overview of the mussel miRNome based on 5,175,567 non-redundant miRNA reads were obtained. The expression analyses showed opposite results in the transcriptome and miRNome; LPS was the stimulus that triggered the highest transcriptomic response, with 648 differentially expressed genes (DEGs), while poly I:C was the stimulus that triggered the highest miRNA response, with 240 DE miRNAs. Our results reveal a powerful immune response to LPS as well as activation of certain immunometabolism- and ageing/senescence-related processes in response to all the immune challenges. Poly I:C exhibited powerful stimulating properties in mussels, since it triggered the highest miRNomic response and modulated important genes related to energy demand; these effects could be related to the stronger activation of these hemocytes (increased phagocytosis, increased NO synthesis, and increased velocity and accumulated distance). The transcriptome results suggest that after LPS stimulation, pathogen recognition, homeostasis and cell survival processes were activated, and phagocytosis was induced by LPS. β-glucans elicited a response related to cholesterol metabolism, which is important during the immune response, and it was the only stimulus that induced the synthesis of ROS. These results suggest a specific and distinct response of hemocytes to each stimulus from a transcriptomic, miRNomic, and functional point of view.